Anti-NMDA Receptor Encephalitis Presenting with Focal Non-Convulsive Status Epilepticus in a Child - Goldberg, E. M.; Taub, K. S.; Kessler, S. K.; Abend, N. S. (Neuropediatrics, 2011)
A previously healthy 9-year-old girl presented to an emergency department (ED) with headache, dizziness, blurry vision, and abnormal visual perceptions. She was diagnosed with migraine, treated symptomatically, and discharged. Over the course of days, she became progressively somnolent, and returned to the ED, where she was found to have a right inferior quadrantanopsia and sixth nerve palsy. Magnetic resonance imaging (MRI) of the brain showed gyral swelling of the left parieto-occipital lobe. Continuous electroencephalogram (EEG) monitoring revealed focal non-convulsive status epilepticus (NCSE) in the left occipital region. Cerebrospinal fluid (CSF) was positive for antibodies directed against the N-methyl-d-aspartate receptor (NMDAR). This case is the first report of anti-NMDAR encephalitis presenting with focal non-convulsive status epilepticus (NCSE).
Keywords: status epilepticus; encephalitis; pediatric medicine; NMDA; non-convulsive status epilepticus